Resilient virtual communication networks using multi-commodity flow based local optimal mapping. (15th May 2018) - Yang, Qiang; Li, Wei; de Souza, Jose Neuman; Zomaya, Albert Y.
Abstract: Network virtualization has been considered a promising approach for promoting heterogeneous services and mechanisms towards the next-generation network architectures, which can greatly improve the global utilization efficiency of network resources, and hence the capacity of service delivery. However, virtual network invulnerability has long been ignored and little research effort has been made. In this paper, we presented a novel virtual network restoration approach, MFP-VNMH, which could enhance the VN mapping and service restoration subject to the physical link failure in the physical substrate whilst avoiding the remapping of the overall VNs. The performance of proposed MFP-VNMH is assessed through extensive numerical experiments for a range of network scenarios in comparison with the overall VN remapping approach and the end-to-end link remapping approach. The result is encouraging and demonstrates its effectiveness and efficiency for VN mapping update and service restoration upon physical substrate failures.